Indian agriculture towards 2030 - Ramesh, Ramesh; Joshi, Pramod Kumar; Khadka, Shyam (Springer, 2022)
This open access book brings together varying perspectives for transformational change needed in India’s agriculture and allied sectors. Stressing the need of thinking for a post-Green Revolution future, the book promotes approaching this change through eight broad areas, indicating the policy shifts needed to meet the challenges for the coming decade (2021-2030). The book comprises of ten contributions. Apart from the overview chapter on transformational change and the concluding chapter on pathways for 2030, there are eight thematic chapters on topics such as transforming Indian agriculture, dietary diversity for nutritive and safe food; climate crisis and risk management; water in agriculture; pests, pandemics, preparedness and biosecurity natural farming; agroecology and biodiverse futures; science, technology and innovation in agriculture; and structural reforms and governance. The writing style of these papers written by technical experts is forward-looking—not merely an analysis of what has been and why it was so, but what ought to be. This is an essential reading for those interested in agriculture, food and nutrition sectors of India, and more so their interconnectedness.